Method for preparing hard carbon negative electrode material rich in micro-sodium pore structure by using biological fermentation method and application of hard carbon negative electrode material

The preparation of hard carbon materials rich in micro-sodium pore structures through biofermentation method has solved the problem of limited electrochemical performance of existing hard carbon materials in sodium ion batteries, and achieved efficient and stable sodium ion charging and discharge and excellent electrochemical performance.

CN119612487APending Publication Date: 2025-03-14DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775842.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The electrochemical performance of existing hard carbon materials in sodium ion batteries is limited by pore inhomogeneity and structural instability, making it difficult to achieve efficient and stable sodium ion charging and discharge.

Method used

Biofermentation method is used to prepare hard carbon negative electrode materials with micro-sodium pore structures. By crushing biomass raw materials, oxygen-free pre-calcining, calcining, mixing with starch and sugar substances, adding microbial flora for fermentation, alcohol washing, calcining coating and airflow crushing, etc., a hard carbon material with a uniform pore structure is formed.

Benefits of technology

The electrochemical properties of hard carbon materials have been significantly improved, including battery capacity, rate performance and long cycle stability, and the conductivity and cycle stability of the material have also been greatly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612487A_ABST
    Figure CN119612487A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hard carbon negative electrode material rich in micro-sodium pore structures by using a biological fermentation method and application, and relates to the technical field of sodium ion battery negative electrode materials. The microbial flora is added into the viscous pasty material, hyphae generated by fermentation of the microbial flora can effectively enter structural gaps of hard carbon, rich and uniform pores can be reserved after calcination, and it can be ensured that the hard carbon material rapidly achieves efficient transmission of ions and electrons. In addition, a double-layer carbon-coated hard carbon material formed by a calcination coating process is coated with pore inner-layer carbon and hard carbon outer-layer carbon. Wherein the porous carbon coating structure can ensure that the hard carbon material can quickly and efficiently realize high-efficiency transmission of ions and electrons, and the conductivity and the cycling stability of the material are greatly improved; the outer carbon-coated structure can improve the overall conductivity of the material, protect the structural integrity of the material, and prevent structural damage caused by volume expansion or shrinkage, thereby improving the cycling stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a method for preparing a hard carbon negative electrode material with a micro-sodium pore structure by using a biological fermentation method and an application thereof. Background Art

[0002] In recent years, with the introduction and implementation of various carbon emission policies, sodium-ion batteries have gained great interest due to their abundant and huge resource reserves and similar properties to lithium-ion batteries, making them a promising competitor for large-scale energy storage.

[0003] The synthesis of negative electrode materials is widely considered to be a major challenge. Among many materials, hard carbon stands out because of its large interlayer spacing, rich sodium storage active sites and unique pore structure. However, the performance of hard carbon materials depends largely on their structure and composition. For the structural parameters of hard carbon, closed micropore structure and interlayer spacing are two key factors affecting the sodium ion storage capacity and ion transport power.

[0004] During traditional hard carbon synthesis, due to the structural instability defects of the raw materials after firing, the pores contained are uneven, and it is impossible to provide efficient and stable sodium ion charging and discharging insertion and escape channels, which affects its electronic conductivity. Therefore, the existing mainstream process plans to start from the carbon coating of the material, using polyvinyl pyrrolidone (PVP) coating method, hydrothermal reaction of sugar and materials and other methods to carry out carbon coating process on hard carbon materials. However, in the above methods, the carbon coating layer produced by the sugar coating method is relatively thin, and it still cannot solve the problems of pore uniformity and structural stability. PVP can only form a carbon layer on the surface of the material, and cannot penetrate into the channels in the hard carbon pores for coating. Therefore, the existing process still fails to solve the problem of fully adaptable and comprehensive improvement of the electrochemical performance of hard carbon materials.

[0005] Based on the above reasons, this application is hereby filed. Summary of the invention

[0006] In view of the problems or defects of the above-mentioned prior art, the purpose of the present invention is to provide a method and application of preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation.

[0007] In order to achieve the above-mentioned purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a hard carbon negative electrode material rich in micro-sodium pore structure by using a biological fermentation method, the method specifically comprising the following steps:

[0009] (1) crushing the biomass raw material to a size not exceeding 100 microns to obtain a dust-like material;

[0010] (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized carbon material;

[0011] (3) calcining the pre-carbonized material in step (2) at 1000-1200° C. for 3-4 hours according to the ratio, and cooling to room temperature after calcination to obtain a calcined product;

[0012] (4) mixing the obtained calcined product with starch and sugar, and grinding them thoroughly; then adding a coagulant to the obtained mixture, and stirring until a viscous paste is obtained;

[0013] (5) placing the viscous paste material in a closed environment, adding microbial flora according to a ratio, stirring evenly, and standing at a temperature of 50-75° C. for 6-24 days to undergo a fermentation reaction; after the fermentation reaction is completed, sequentially undergoing alcohol washing, calcination coating, and air flow pulverization to obtain a hard carbon negative electrode material rich in micro-sodium pore structure.

[0014] Furthermore, in some embodiments, the biomass raw material in step (1) can be one or more of coconut shells, bamboo, hard fruit shells, straw, grass leaves, etc. These biomass raw materials are abundant in source and have high carbon yield.

[0015] Specifically, in the above technical solution, the purpose of the oxygen-free pre-calcination in step (2) is to discharge the tar in the hard carbon raw material to obtain a pre-carbonized material.

[0016] Furthermore, in the above technical solution, the time for the oxygen-free pre-calcination treatment in step (2) is 3-5 hours, preferably 4 hours.

[0017] Furthermore, in the above technical solution, during the anaerobic pre-calcination treatment in step (2), a protective gas may be introduced into the reaction system to accelerate the discharge of tar by purging with the protective gas.

[0018] Furthermore, in the above technical solution, the flow rate of the protective gas is 1-5 ml / s.

[0019] Furthermore, in the above technical solution, the protective gas is argon.

[0020] Furthermore, in the above technical solution, the starch material in step (4) is a mixture of one or more of corn starch, potato starch, rice starch, wheat starch, etc.

[0021] Furthermore, in the above technical solution, the sugar substance in step (4) is a mixture of one or more of glucose, fructose, sucrose, etc.

[0022] Furthermore, in the above technical solution, the mass ratio of the calcined product to the starchy substance and the sugar substance in step (4) is 5-10:3-10:1.

[0023] Furthermore, in the above technical solution, the coagulant in step (4) consists of deionized water and a thickener; wherein the thickener is a mixture of one or more of carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), etc.

[0024] Furthermore, in some embodiments of the present invention, the mass ratio of the thickener to deionized water is 1:1-3.

[0025] Furthermore, in some embodiments of the present invention, the coagulant is prepared by the following method: deionized water and a thickener are mixed according to a ratio, and stirred until they become a glue-like state.

[0026] Furthermore, in the above technical solution, the mass ratio of the mixture in step (4) to the thickener in the coagulant is 100:1-8, preferably 100:3-5.

[0027] Furthermore, in the above technical solution, the microbial flora in step (5) is a mixture of one or more bacteria selected from photosynthetic bacteria, lactic acid bacteria, yeasts or actinomycetes.

[0028] Furthermore, in the above technical solution, the mass ratio of the microbial flora to the dust-like material in step (5) is 1:100-300.

[0029] Furthermore, in some embodiments, during the fermentation reaction in step (5), stirring is preferably performed every 12 hours.

[0030] Furthermore, in some embodiments, the calcination temperature used for the calcination coating in step (5) is 400-600° C., and the calcination time is 6-12 hours.

[0031] Furthermore, in some embodiments, the specific process of the airflow crushing in step (5) is as follows: the airflow pressure is controlled to be 0.7 MPa, the feed rate is 2 kg / h, and the gas flow rate is 6 square meters / minute.

[0032] The second object of the present invention is to provide a hard carbon negative electrode material with a micro-sodium pore structure prepared by the above method.

[0033] The third object of the present invention is to provide the application of the hard carbon negative electrode material rich in micro-sodium pore structure prepared by the above method in sodium ion batteries.

[0034] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the negative electrode is a hard carbon negative electrode material rich in micro-sodium pore structure prepared by the above-mentioned method.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention adds microbial flora to the viscous paste material. The mycelium produced by the fermentation of these microbial flora can effectively enter the structural gaps of the hard carbon, leaving abundant and uniform pores after calcination, thereby ensuring that the hard carbon material can quickly realize the efficient transmission of ions and electrons.

[0037] (2) The present invention can introduce nitrogen elements during the fermentation process of the hard carbon structure through a mild and green fermentation pretreatment process, so that the structure of the biomass changes, the interlayer spacing is expanded, more reaction sites are generated, and uniform gaps are obtained, thereby effectively improving the electrochemical performance (battery capacity and rate performance). The sugar substances used during fermentation are not only important components to promote fermentation, but also present as carbon sources in the final material. Adding organic substances such as CMC, HEC, and HPMC not only plays a thickening role, but also enhances the full sauce-forming of fungi and hard carbon materials.

[0038] (3) The calcination coating process adopted by the present invention allows the biomass around the hard carbon material and in the pores to be rapidly carbonized, forming a double-layer carbon-coated hard carbon material with an inner carbon coating in the pores and an outer carbon coating in the hard carbon. Among them: the pore carbon coating structure can ensure that the hard carbon material can quickly and efficiently realize the efficient transmission of ions and electrons, greatly improving the electrical conductivity and cycle stability of the material; the outer carbon coating structure can improve the overall electrical conductivity of the material, protect the structural integrity of the material, and prevent structural damage caused by volume expansion or contraction, thereby improving the cycle stability of the material.

[0039] (4) The present invention provides a method of using biological fermentation technology to form a hard carbon material after two-step calcination of hard carbon raw materials, and then using green biological mild fermentation technology for post-treatment coating, and then high-temperature calcination to carbonize the microorganisms, so that micro-sodium carbon can be coated inside and outside the pores of the hard carbon material to improve the stability and electrochemical performance of the material. The method of the present invention selects one or more raw materials with high carbon content such as coconut shells, bamboo, hard fruit shells, straw, and grass leaves, and crushes and combines them. Various types of biomass starch and a wide range of sugar substances with low cost and strong renewable degree are used as carbon sources. Viscosity agents and various bacterial communities are added, and after auxiliary fermentation, calcination is performed to prepare micro-sodium porous carbon-coated hard carbon materials with better electrochemical properties.

[0040] (5) The present invention introduces fungal proliferation on the hard carbon material through a mild and green fermentation process to produce decomposition enzymes, so that the fungal biomass (such as hyphae) can proliferate and spread rapidly, and while wrapping around the hard carbon material, it simultaneously fills the pores of the material structure to achieve a strong support effect. After that, the biomass can be quickly carbonized by calcination to achieve a carbon coating effect around the material and in the pores. The effect is manifested in that the initial reversible capacity, rate performance and long-cycle stability can be significantly improved. The firm and uniform carbon-coated pore structure can also ensure that the hard carbon material can quickly and efficiently realize the efficient transmission of ions and electrons, which greatly improves the electrical conductivity and cycle stability of the material.

[0041] (6) The hard carbon negative electrode material rich in micro-sodium pore structure prepared by the present invention is applied to sodium ion batteries, which has excellent cycle stability: the capacity decays to 92% after 2000 cycles. In addition, the hard carbon negative electrode material rich in micro-sodium pore structure prepared by the present invention also has excellent discharge capacity, and the highest first discharge capacity reaches 313 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The test diagram of the charge and discharge cycle of a half-battery composed of hard carbon material as positive electrode and sodium sheet as negative electrode;

[0043] Figure 2 This is the XRD pattern of the hard carbon negative electrode material with micro-sodium pore structure prepared in Example 1. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0045] Based on the information contained in this application, it is easy for those skilled in the art to make various changes to the precise description of the present invention without departing from the spirit and scope of the appended claims. It should be understood that the scope of the present invention is not limited to the defined process, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention. In fact, various changes that the technicians in this field or related fields can obviously make to the embodiments of the present invention are all covered within the scope of the appended claims.

[0046] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0047] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0048] Example 1

[0049] The present embodiment provides a method for preparing a hard carbon negative electrode material with a micro-sodium pore structure by using a biological fermentation method, the method specifically comprising the following steps:

[0050] 1. Preparation of hard carbon

[0051] 1) Crushing: Coconut shells and straws are mixed in a raw material ratio of 1:1 by mass, and crushed to reduce the particle size to no more than 50 microns to obtain a dust-like material.

[0052] 2) Anaerobic pre-calcination: Anaerobic pre-calcination: The crushed dust-like material is sent into a box furnace in an argon atmosphere for pre-carbonization. The temperature is heated from room temperature, and is increased stepwise by 0.5 degrees Celsius per minute to 550 degrees Celsius and kept at this temperature for 3 hours. The temperature is then lowered by 0.5 degrees Celsius per hour to 25 degrees Celsius to obtain a pre-carbonized carbon material and discharge tar.

[0053] 3) High-temperature calcination: The pre-calcined carbonized material is placed in an orbital furnace and heated in a step-by-step manner at a heating rate of 2 degrees Celsius per minute until it reaches 1200 degrees Celsius. The temperature is then kept at this temperature for three hours and then cooled to room temperature at a rate of 2 degrees Celsius per minute.

[0054] 2. Biological post-treatment

[0055] 4) Preparation of a coagulant: 6 g of carboxymethyl cellulose (CMC) was selected, mixed with deionized water in a mass ratio of 1:1.5, and stirred thoroughly until a paste was formed to obtain a coagulant for later use.

[0056] 5) Mixing of materials and coagulants: Add 1.2 g corn starch and 0.8 g glucose (mass ratio of hard carbon material: starch material: sugar material = 5:3:2) to 2 g of the hard carbon material obtained by high-temperature calcination in step 3). After sufficient grinding, add the coagulant prepared in step 4) to the resulting mixture and stir for 5 minutes to obtain a viscous paste-like material. The mass ratio of the mixture to the thickener in the coagulant is 100:3.

[0057] 6) Bacteria inoculation: Place the viscous paste obtained in step 5) in a closed environment, add yeast flora, and stir evenly in a ratio of 300:1 between the mass ratio of the dust-like material and the flora.

[0058] 7) Fermentation: Ferment at 65°C for 21 days (stir every 12 hours) until the internal fermentation reaction is complete and the fermentation product is generated.

[0059] 8) Alcohol washing: The fermentation product obtained in step 7) is washed with an ethanol solution to remove excess substances produced by the fermentation.

[0060] 9) Calcination and coating: The cleaned material is placed in a muffle furnace, heated to 400°C and baked for 8 hours to rapidly carbonize the biomass on the surface and in the pores of the hard carbon material, forming a double-layer carbon-coated hard carbon material with an inner carbon coating in the pores and an outer carbon coating in the hard carbon layer.

[0061] 10) Airflow milling: After drying, the material is put into airflow milling for crushing and screening. The specific process of airflow milling is as follows: control the airflow pressure to 0.7MPA, the feed rate to 2kg / h, the gas flow rate to 6 square meters / minute, and the crushed material can be used directly.

[0062] Example 2

[0063] The method of preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation in this embodiment is basically the same as that in Example 1, the only difference is that in step 6) of this embodiment, the mass ratio of dust-like material to bacterial community is 100:1, and the others remain unchanged.

[0064] Example 3

[0065] The method of preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation in this embodiment is basically the same as that in Example 1, the only difference is that the fermentation time in step 7) of this embodiment is 24 days, and the rest remains unchanged.

[0066] Example 4

[0067] The method of preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation in this embodiment is basically the same as that in Example 1, the only difference is that in step 5) of this embodiment, the mass ratio of the hard carbon material, starch material and sugar material is 5:2:3, and the others remain unchanged.

[0068] Example 5

[0069] The method of preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation in this embodiment is basically the same as that in Example 1, the only difference is that the calcination coating in step 9) of this embodiment is heated to 600°C, and the other steps remain unchanged.

[0070] Figure 1 The charge and discharge cycle diagram of a half-battery composed of hard carbon material as positive electrode and sodium sheet as negative electrode. Figure 1 It can be concluded that the cycle performance of the half-cell prepared by using the hard carbon material rich in micro-nano pore structure prepared in Example 1 as the negative electrode active material is 301g / mAh in the first charge and discharge cycle, and 280g / mAh in the 2000th cycle.

[0071] Figure 2 This is the XRD pattern of the hard carbon material prepared in step 1 of Example 1. It can be seen that the hard carbon material was successfully synthesized.

[0072] The hard carbon negative electrode materials rich in micro-sodium pore structure prepared in the above Examples 1-5 are respectively used as negative electrode active materials to assemble button batteries, and the specific method is as follows:

[0073] The negative electrode sheet is composed of a hard carbon negative electrode material rich in micro-sodium pore structure, Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, wherein the mass ratio of the hard carbon negative electrode material rich in micro-sodium pore structure, Super P, SBR and CMC is 90:2:4:4. The hard carbon negative electrode material rich in micro-sodium pore structure and Super P conductive carbon are ground and mixed evenly for 20 minutes in proportion, and the evenly mixed material and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), placed on a micro ball mill and stirred for 15 minutes to obtain a uniform slurry, and the slurry is evenly coated on aluminum foil (the coating amount is 110.23g / cm 2 ), vacuum dried in an oven at 120°C for 5 hours, and punched out negative electrode sheets with a diameter of 12 mm using a gun press, which were weighed and set aside for use.

[0074] A sodium ion battery half-cell is formed by using a sodium sheet as the positive electrode, the negative electrode is the negative electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 180 mA / g, the test voltage range is 0.05 V-2 V, and the button battery is subjected to a charge and discharge cycle test.

[0075] Figure 1 This is a comparison table of the first charge and discharge cycles of half-cells prepared using the hard carbon materials rich in micro-nano pore structures prepared in Examples 1-5 of the present invention as negative electrode active materials. Table 1 summarizes the first discharge gram capacity of batteries made from materials under different proportions and different temperatures. It can be seen from the summary table that Example 2 is the most advantageous preparation condition for the material.

[0076] Table 1 Comparison of the first charge and discharge cycles of half-cells prepared using the hard carbon materials rich in micro-nano pore structures prepared in Examples 1-5 of the present invention as negative electrode active materials

[0077] Example First cycle capacity (g / mAh) Capacity after 2000 cycles (g / mAh) Capacity retention rate (%) Example 1 301 280 93 Example 2 313 297 95 Example 3 298 267 89 Example 4 295 277 89 Example 5 303 291 92

Claims

1. A method for preparing a hard carbon negative electrode material rich in micro-sodium pore structure by biological fermentation, characterized in that: The method specifically comprises the following steps: (1) crushing the biomass raw material to a size not exceeding 100 microns to obtain a dust-like material; (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized carbon material; (3) calcining the pre-carbonized material in step (2) at 1000-1200° C. for 3-4 hours according to the ratio, and cooling to room temperature after calcination to obtain a calcined product; (4) mixing the obtained calcined product with starch and sugar, and grinding them thoroughly; then adding a coagulant to the obtained mixture, and stirring until a viscous paste is obtained; (5) placing the viscous paste material in a closed environment, adding microbial flora according to a ratio, stirring evenly, and standing at a temperature of 50-75° C. for 6-24 days to undergo a fermentation reaction; after the fermentation reaction is completed, sequentially undergoing alcohol washing, calcination coating, and air flow pulverization to obtain a hard carbon negative electrode material rich in micro-sodium pore structure.

2. The method according to claim 1, characterized in that: The biomass raw material in step (1) can be one or more of coconut shells, bamboo, hard fruit shells, straw, and grass leaves.

3. The method according to claim 1, characterized in that: The starch material in step (4) is a mixture of one or more of corn starch, potato starch, rice starch, and wheat starch; the sugar material in step (4) is a mixture of one or more of glucose, fructose, and sucrose.

4. The method according to claim 1, characterized in that: In step (4), the mass ratio of the calcined product to the starchy substance and the sugar substance is 5-10:3-10:

1.

5. The method according to claim 1, characterized in that: The coagulant in step (4) is composed of deionized water and a thickener; wherein the thickener is a mixture of one or more of carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), etc.

6. The method according to claim 1, characterized in that: The microbial flora in step (5) is a mixture of one or more of photosynthetic bacteria, lactic acid bacteria, yeast or actinomycetes.

7. The method according to claim 1, characterized in that: The calcination temperature used for the calcination coating in step (5) is 400-600° C., and the calcination time is 6-12 hours.

8. A hard carbon negative electrode material with micro-sodium pore structure prepared by the method according to any one of claims 1 to 7.

9. Application of the hard carbon negative electrode material rich in micro-sodium pore structure prepared by the method according to any one of claims 1 to 7 in sodium ion batteries.

10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a hard carbon negative electrode material with a micro-sodium pore structure prepared by the method described in any one of claims 1 to 7.